The gut as an inductive site for synovial and extra-articular immune responses in rheumatoid arthritis. Issue 6 (June 1994) - Trollmo, C; Sollerman, C; Carlsten, H; Tarkowski, A
Abstract : OBJECTIVES--To analyse the immunological interactions between the gut lymphoid tissue, synovium, and peripheral blood compartments in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). METHODS--Patients with RA and AS and healthy controls were orally or parenterally immunised with an influenza virus vaccine. Antigen-specific antibody responses were measured at the single cell level by ELISPOT assay using lymphocytes isolated from peripheral blood and from enzymatically dispersed synovial tissues. RESULTS--Both oral and parenteral immunisations induced antigen-specific antibody-secreting cells in the synovial tissue of patients with RA. Parenterally immunised patients with RA showed significantly decreased antigen-specific antibody responses in peripheral blood compared with patients with AS and with healthy controls. In contrast, oral vaccination evoked comparable peripheral blood antibody responses in all three study groups. CONCLUSIONS--Despite a decreased immune responsiveness in the systemic compartment, the functional status of the gut-associated lymphoid tissue in patients with RA is intact. In addition, there is evidence that the lymphocytes in the inflamed joints are accessible for signals both from the systemic and mucosal compartments. The findings of immunological 'cross-talk' are relevant to future vaccination and tolerization procedures in patients with RA.